Broker Organizations to Facilitate Cross‐Sector Collaboration: At the Crossroad of Strengthening and Weakening Effects. - Stadtler, Lea; Karakulak, Özgü (Public Administration Review, 2020)
Cross‐sector collaboration has emerged as an important way for public management to address complex social issues. Given the manifold challenges of governing and implementing such collaborations, scholars emphasize the benefits of using broker organizations to facilitate and strengthen cross‐sector collaboration. However, this comparative longitudinal case study of broker organizations that support global health partnerships shows a less straightforward pattern: despite their good intentions, two of the four broker organizations analyzed subtly weakened the collaboration by gradually replacing the partners' cross‐sector tasks and decision‐making with unilateral, broker‐based ones. By juxtaposing this pattern with the other two broker organizations' trajectories, this study reveals the processes underlying brokers' role drift and unintended collaborative weakening and those allowing them to maintain their facilitation role. On this basis, the study exposes overlooked collaboration dynamics to reveal the boundaries of using broker organizations as a mechanism to facilitate cross‐sector collaboration.